Anatomy of a deformed upper crust fragment from western Alpine Corsica (France): insights into continental subduction processes. Issue 1 (2nd January 2023) - Frassi, Chiara; Di Rosa, Maria; Farina, Federico; Pandolfi, Luca; Marroni, Michele
ABSTRACT: In Corsica Island (France), a belt of metamorphic continental units derived from the European margin is exposed at the western rim of the Alpine Corsica. This study provides a complete anatomy of one of these units (Tour de Valletto Unit) consisting of a Palaeozoic basement covered by an Early Jurassic – late Eocene sedimentary succession. This unit records a polyphase tectono-metamorphic history acquired during the late Eocene – lower early Miocene convergence processes involving the Adria and Europe continental plates. Using a multidisciplinary approach, we reconstructed in detail the P-T path of the Tour de Valletto Unit. The path shows a metamorphic climax at blueschist facies conditions suggesting that the unit was accreted at c. 40 km of depth. After its accretion, the Tour de Valletto Unit was exhumed up to the Earth surface following a path characterized by an increase of temperature and a decrease of pressure. The reconstructed tectono-metamorphic history of the Tour de Valletto Unit is compared with those of the other continental units located in western Alpine Corsica to discuss the exhumation processes active during continental subduction.